Assessing the soil physical and chemical properties of long-term pomelo orchard based on tree growth - Linh Tran Ba; Thang La Cao; Khoi Chau Minh; Phuong Nguyen Thi Kim; Thuc Le Vinh (Open Agriculture)
The investigation in three groups of pomelo trees (good, average, bad) was conducted. Each group included 15 orchards. The number of soil samples collected for analysis is 15 samples × 2 depths (0–15 cm and 15–30 cm) × 3 groups of plants = 90 soil samples. The results indicated that the soil texture of the good pomelo orchard group and the average pomelo orchard group is silty clay loam, and the bad pomelo orchard group has a silty clay. The average pH value in the bad pomelo orchard group is lower than the average pomelo orchard group and the good pomelo orchard group at both soil depths of 0–15 cm and 15–30 cm. The soil EC of the three groups of pomelo orchards is not different at depths of 0–15 cm and 15–30 cm and does not affect the plants. The average organic matter content at both soil depths 0–15 cm and 15–30 cm of the good pomelo orchard group shows the highest organic matter value. Soil bulk density in the group of bad pomelo orchards had the highest value at both depths of 0–15 cm and 15–30 cm. The porosity of the good pomelo orchard group has the highest value at two depths, 0–15 cm and 15–30 cm. Field capacity of good pomelo orchards have the highest values at both depths of 0–15 cm and 15–30 cm. The K sat at a depth of 0–15 cm of the good pomelo orchard group is quite slow, while the average pomelo orchard group and the bad pomelo orchard group are at a slow level. The bad physical and chemical properties had negative effects on pomelo growth.